Mexico, Myth, Politics, Pollock: The Birth of an American Art - Elizabeth L. Langhorne (Arts)
Challenging the still widespread modernist and Eurocentric understanding of Pollock’s art as a formal advance based in Picasso’s cubism, this study explores the pervasive impact of Mexican art, political culture, and myth on the creation of Pollock’s Birth c. 1941. The recent discovery of Pollock’s early exposure to Diego Rivera’s use of the Mesoamerican myth of Quetzalcoatl invites a reconsideration of the sources of his art. The myth of Quetzalcoatl challenged Pollock, who responded not just to Rivera but also to Siqueiros’ understanding of the political significance of art and to Orozco’s call for Quetzalcoatl’s return in a modern migration of the spirit at Dartmouth College. Made aware of the positive potential of this mythic symbolism by his Jungian psychotherapy, we see Pollock using it to counter the destructive force of fascism depicted in Picasso’s Guernica 1937. In the process he discovers his own artistic identity in Birth as a mythmaker in a time of war, capable of generating new Pan-American symbols and forms to challenge the hegemony of Picasso.